1963
DOI: 10.1172/jci104869
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function in the Newborn Infant. V. Trapped Gas in the Normal Infant's Lung*

Abstract: "Trapped gas" has been defined by Bedell, Marshall, DuBois, and Comroe (1) as "that component of the thoracic gas volume which, having entered the thorax, is present in the lungs or pleural space but is unable to leave owing to intrapulmonary mechanical factors which prevent gaseous outflow." By measuring the ventilated portion of the thoracic gas volume (i.e., the functional residual capacity, FRC) with conventional dilutional methods (2) and comparing it to the total (ventilated and nonventilated) thoracic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2

Year Published

1966
1966
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 17 publications
1
23
2
Order By: Relevance
“…The FRC values related to weight or length are lower than some of the previously published figures for neonates and infants (6)(7)(8)(9)(10)(12)(13)(14) but most of these data were TGV obtained by plethysmography (Table 1). Larger values for TGV than for FRC measured by He-dilution or N2 washout have been noted before and attributed to gas trapping (1 3-15).…”
Section: Discussioncontrasting
confidence: 63%
“…The FRC values related to weight or length are lower than some of the previously published figures for neonates and infants (6)(7)(8)(9)(10)(12)(13)(14) but most of these data were TGV obtained by plethysmography (Table 1). Larger values for TGV than for FRC measured by He-dilution or N2 washout have been noted before and attributed to gas trapping (1 3-15).…”
Section: Discussioncontrasting
confidence: 63%
“…The FRC values found in the present study [III] When measuring lung volume concurrently with the nitrogen-washout and the plethysmo graphic technique in the same individual, Nelson et al (1963 a] found, however, sig nificantly higher values in 10 out of 22 in fants with the plethysmographic method. They concluded, since the N2 and the Flemethod measure the ventilated portion of the thoracic gas volume, i. e. true FRC, and the plethysmographic technique total thoracic gas volume, that some healthy infants may have significant amounts of trapped air, i. e. airway obstruction.…”
Section: Further Development Of Pulmonary Mechanics and Lung Volumecontrasting
confidence: 53%
“…However, this does not reflect the wide scatter of results observed within many of the studies, which must be borne in mind when interpreting results. The discrepancy between gas dilution and plethysmographic techniques has been largely attributed to the presence of trapped gas, which is not detected by gas equilibration methods [45][46][47][48]. However, there have been relatively few high quality comparative studies on sufficiently large numbers of infants to clarify this issue.…”
Section: Reference Values In Infantsmentioning
confidence: 99%
“…Despite recently renewed interest in the nitrogen washout technique, particularly with respect to its application in the intensive care unit [49], very limited data are available for healthy infants and children [47,50]. GERHARDT et al [51] studied 50 children over the first 5 yrs of life (14 of whom were less than 1 month old), and found a high correlation between FRC and body length.…”
Section: Reference Values In Infantsmentioning
confidence: 99%